A Study of Speededness as a Source of Test Bias - Evans, Franklin R.; Reilly, Richard; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Specially constructed "speeded" and "unspeeded" forms of a Reading Comprehension section of the Law School Admission Test (LSAT) were administered to regular center and fee-free center LSAT candidates in an effort to determine: (1) if the test was more speeded for fee-free candidates, and (2) if reducing the amount of speededness was more beneficial to fee-free candidates. Results of the analysis show: (1) the test is somewhat more speeded for fee-free candidates than for regular candidates, (2) reducing the amount of speededness produces higher scores for both regular (22 scaled score points) and fee-free (33 scaled score points) center candidates, and (3) reducing speededness is not more beneficial (in terms of increasing the number of items answered correctly) to fee-free than to regular center candidates. Lower KR-20 reliability was observed under speeded conditions in the fee-free sample and is discussed. (Author)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Blacks; Fees; Financial Support; Item Analysis; Reading Comprehension; Scores; Test Bias; Test Reliability; Test Results; Testing Problems; Tests; Timed Tests; Law School Admission Test